Relationship between tiktok usage and youth well-being involving personality characteristics - Tang, Lian (2022)
TikTok, as one of several social media applications, has attracted numerous users, particularly youths, due to its short and fast video features. By creating a content ecology and recommendation power through algorithms, TikTok enables users with similar interests to expand their social relationships through content sharing, becoming a key trend in social media video applications in China. However, the findings of some past studies have revealed problematic TikTok usage patterns, which have impaired positive emotions and relationships among youth. Moreover, other issues have also been present on TikTok, and these have reduced the level of well-being from using TikTok. Nevertheless, there are limited studies on the relationship between TikTok usage and well-being in China, as TikTok is an emerging social media platform. Therefore, the current study examines how TikTok usage correlates with well-being among youth. The general objective of this study is to examine users’ personality characteristics as a moderating factor toward the relationship between TikTok usage and youth well-being in China. Under the umbrella of TikTok usage, the research has applied the technology acceptance model to study attitudes toward TikTok, and adopted uses and gratifications theory to examine the need for using TikTok. Meanwhile, the PERMA model of well-being theory has been employed to evaluate youths’ overall well-being. This study used a quantitative approach via survey design, collecting a total of 596 self-administered questionnaires from TikTok users in Xi’an, China through four-stage cluster sampling, simple random sampling, and purposive sampling techniques. Data analysis was performed in accordance with structural equation modelling via Smart-PLS software and Statistical Package for the Social Sciences software. The study found that attitudes toward TikTok and needs for using TikTok significantly contributed 71.1% of variance in overall PERMA well-being among youth in China in general. The findings revealed that perceived usefulness and entertainment needs were the main factors that significantly and positively associated with youths’ well-being, followed by social needs, tension release needs, perceived ease of use, and cognitive needs, respectively. This study also found that there was a significant moderating role of personality characteristics on the relationship between perceived ease of use, entertainment needs, and well-being among youth in China. In light of the theoretical contribution, this study illustrated the influence of TikTok usage on youths’ well-being based on the technology acceptance model, uses and gratifications theory, and PERMA model of well-being. In terms of practical aspects, the findings of this research could be helpful for youth development practitioners, families, youths themselves, and TikTok operators. It is recommended that TikTok users (youth) should pay attention to the negative impacts of TikTok usage and exercise caution accordingly when using TikTok in the future.